2019
DOI: 10.1002/ccd.28308
|View full text |Cite
|
Sign up to set email alerts
|

Impact of intravascular ultrasound‐guided drug‐eluting stent implantation on patients with chronic kidney disease: Results from ULTIMATE trial

Abstract: Objectives This study aimed to investigate the impacts of intravascular ultrasound (IVUS)‐guided drug‐eluting stent (DES) implantation on patients with chronic kidney disease (CKD) based on the ULTIMATE trial. Background IVUS‐guided DES implantation improves clinical outcomes in complex lesions. However, routine IVUS guidance in patients with CKD remains controversial. Methods CKD was defined as an estimated glomerular filtration rate (eGFR) <60 mL min−1 1.73 m−2. The primary end point was target vessel failur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 28 publications
(50 reference statements)
0
11
0
Order By: Relevance
“… 9 A substudy from the ULTIMATE (Intravascular Ultrasound Guided Drug Eluting Stents Implantation in “All‐Comers” Coronary Lesions) randomized trial demonstrated lower target vessel failure (TVF) (hazard ratio [HR], 0.12 [95% CI, 0.02–0.93]) and target vessel MI (HR, 0.12 [95% CI, 0.02–0.93]) with IVUS use compared with angiography guided PCI among 349 patients with chronic kidney disease. 18 However, the hazards for other outcomes, including mortality, were either insignificant or incalculable because of their small sample size. While our findings suggest that ICI was associated with lower in‐hospital mortality in cases with an EAPCI imaging‐recommended indication, this was only the case with certain indications including renal failure, stent thrombosis, LMS PCI, ACS indication, and stent length >60 mm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 9 A substudy from the ULTIMATE (Intravascular Ultrasound Guided Drug Eluting Stents Implantation in “All‐Comers” Coronary Lesions) randomized trial demonstrated lower target vessel failure (TVF) (hazard ratio [HR], 0.12 [95% CI, 0.02–0.93]) and target vessel MI (HR, 0.12 [95% CI, 0.02–0.93]) with IVUS use compared with angiography guided PCI among 349 patients with chronic kidney disease. 18 However, the hazards for other outcomes, including mortality, were either insignificant or incalculable because of their small sample size. While our findings suggest that ICI was associated with lower in‐hospital mortality in cases with an EAPCI imaging‐recommended indication, this was only the case with certain indications including renal failure, stent thrombosis, LMS PCI, ACS indication, and stent length >60 mm.…”
Section: Discussionmentioning
confidence: 99%
“… 2 , 20 , 21 , 22 Similarly, the use of ICI in patients with renal failure minimizes their exposure to higher volumes of contrast and subsequent risk of contrast‐induced nephropathy, which is independently associated with higher mortality and MACE, as well as minimizes their risk of future stent failure. 18 , 23 …”
Section: Discussionmentioning
confidence: 99%
“…The next step forward appeared to be Zhang’s trial [ 24 ], in which study populations consisted only of CKD patients (in fact, it was a post-hoc analysis from the ULTIMATE trial) [ 25 ], and the comparison was between standard and IVUS-guided procedures. Likewise, the idea of low-contrast procedures in CKD was not taken into account.…”
Section: Discussionmentioning
confidence: 99%
“…The method and results of ULTIMATE trial have been reported previously [14,15]. This trial was performed in accordance with Declaration of Helsinki and International conference, and the protocol was approved by the ethics committee of each participating center.…”
Section: Patientsmentioning
confidence: 99%